Association of skin-advanced glycation end products, IMT complex, and bone mineral density in patients with type 1 diabetes - Zawada, Agnieszka; Naskret, Dariusz; Grzelka-Woźniak, Agata; Ratajczak-Pawłowska, Alicja E.; Rychter, Anna M.; Skoracka, Kinga; Michalak, Michał; Szymczak-Tomczak, Aleksandra; Zozulinska-Ziolkiewicz, Dorota; Dobrowolska, Agnieszka; Krela-Kaźmierczak, Iwona (Frontiers in Endocrinology, 2025)
IntroductionThe accumulation of protein glycation end products, in addition to the direct impact of hyperglycemia, represents one of the most common pathomechanisms involved in the development of osteoporosis in diabetic patients. This study aimed to evaluate the accumulation of advanced glycation end products (AGEs) in the skin and the thickness of the intima/media complex (IMT) in patients with type 1 diabetes in relation to bone mineral density.Materials and methodsThe study comprised a group of 132 individuals, including diabetes mellitus type 1 (DM1) patients. The thickness of the IMT complex was evaluated. Bone mineral density (BMD), T-score, and Z-score were assessed using dual-energy X-ray absorptiometry. Skin AGE assessment was performed by AGE-Reader.ResultsThe concentration of AGEs in the skin was significantly higher in patients with DM1 and osteopenia in the femoral neck as compared to individuals with diabetes and normal bone mass, as well as with the control group. The thickness of the IMT complex was significantly greater in subjects with diabetes compared to healthy participants, regardless of osteopenia in the femoral neck and L1-L3.ConclusionPatients with DM1 demonstrated lower BMD in L1–L4 and in the femoral neck compared to those in the non-diabetic group. Patients with type 1 diabetes mellitus and osteopenia did not present a statistically significant increase in the thickness of the IMT complex compare to those with DM1 without osteopenia. Individuals with coexisting DM1 and osteopenia in the femoral neck, but not in L1–L4, presented significantly higher values of skin AGEs than participants with diabetes mellitus without bone mineral disorders.